A nanobiosensing method based on force measurement of antibody-antigen interaction for direct detection of enterovirus 71 by the chemically modified atomic force microscopic probe. (October 2017) - Hong, Chung-Hung; Hsieh, Chung-Fan; Tseng, Chi-Shin; Huang, Wei-Chih; Guo, Cheng-Yan; Lin, Shiming; Lee, Si-Chen
Abstract: Hand, Foot and mouth disease (HFMD) is a common disease with high infectivity for children, and enterovirus 71 (EV71) is one of the main pathogens to cause the type of illness. Therefore, the aim of this study was to propose a rapid and effective technique for detecting EV71 directly based on the mechanism of biological intermolecular force by using atomic force microscopy (AFM). At first, we coated EV71 particles on the mica surface and made the EV71 antibodies ( anti -EV71) fixed on the AFM tip by means of several chemical procedures. Then, AFM chemically modified tip was applied to measure the unbinding forces between EV71 and anti -EV71 by contact mode. Finally, by using AFM imaging calculating software, the EV71 particle size (mean ± SD) was 31.36 ± 3.87 nm (n = 200) and this result was concordance with previous literature. Besides, the force (mean ± SD) between EV71 antigen and antibody complex was 336.9 ± 64.7 pN. The force (mean ± SD) between anti -EV71 and non-specific specimens was 47.1 ± 15.1 pN and was significantly smaller (P < 0.05). Apparently, the results show that we can precisely identify EV71 infection among the samples by measuring the force magnitude and observing the occurrence of EV71/ anti -EV71 unbinding events. Therefore, the combination of AFM system and the chemically modified tip has the potential to be a rapid and effective method for detecting EV71 directly. Highlights: A rapid, quantitative, and direct approach for enterovirus 71 (EV71) detection was developed. The unbinding force between EV71 antigen and its antibody was directly observed by the chemically modified AFM tip. The appearance of EV71 particle was directly observed by AFM tapping mode.